ЎҚУВЧИЛАРНИНГ КАСБИЙ ҚИЗИҚИШЛАРИ: МУАММО ВА ЕЧИМЛАР - Нишанова, З.Т.; Алимова, Г.К. (SCIENCE and SOCIETY, 2017)
The article presents the professional orientation games and exercises that can be used by school and boarding school psychologists.